Sulindac increases the expression of APC mRNA in malignant colonic epithelial cells: an in vitro study. Issue 5 (May 1996) - Schnitzler, M; Dwight, T; Robinson, B G
Abstract : BACKGROUND--Sulindac is a non-steroidal anti-inflammatory drug which induces regression of colonic polyps in patients with familial adenomatous polyposis. Animal and in vitro studies have shown that both the sulphide metabolite of sulindac, which is able to inhibit cyclo-oxygenase, and the sulphone metabolite, which lacks this ability, are able to inhibit the growth of colonic carcinoma cells. The exact mechanism by which these effects occurs is not known. AIMS--To examine the effect of sulindac sulphide and sulindac sulphone on the expression of APC messenger RNA (mRNA), and on the proliferation of colonic carcinoma cells in vitro. METHODS--The colonic carcinoma cell line LIM 1215 was treated with sulindac sulphide and sulindac sulphone (10 microM or 100 microM) for 24 hours. Total RNA was extracted and APC mRNA was quantitated using competitive reverse transcription polymerase chain reaction. Measurements of cell number, cell proliferation, and prostaglandin E2 concentrations were also made. RESULTS--A significant increase in APC mRNA was observed after treatment with 10 microM of both sulindac sulphide and sulindac sulphone (control: 37.2 (19.7); 10 microM sulindac sulphide: 129 (112.8); 10 microM sulindac sulphone: 207.7 (102.9) pg/(g total RNA) (p < 0.05). Prostaglandin E2 concentrations were significantly reduced after treatment with sulindac sulphide, but not after sulindac sulphone. Both agents produced a dose dependent reduction in cell numbers and cell proliferation, which was more noticeable after treatment with sulindac sulphide. CONCLUSIONS--Both sulindac sulphide and sulindac sulphone inhibit the growth of carcinoma cells in vitro and cause an increase in APC mRNA. The effect of these agents on colonic carcinogenesis is not mediated entirely by means of an inhibition of prostaglandin biosynthesis.